Alternative Local Development models from the periphery - Lopez Oropeza, Mauricio (2013)
As neoliberal capitalism continues to fail on reducing inequities, and continues to fail on fulfilling its promise of a kind of “development” that would allow impoverished men and women to improve their situation and be able to experience a “freedom” which would empower them with new and better opportunities to vanish their many types of “poverties”, new and alternative models raise, presenting a different and inclusive type of development which intends to respond to their particular situations of exclusion and build on an alternative model.